Answer: it makes a horizontal shift. for example: (x-4) means the graph moved 4 units to the RIGHT.
Step-by-step explanation: it is essentially the opposite of what you think if it's inside the parenthesis.
Answer:
9
Step-by-step explanation:
If I’m understanding you correctly, the answer would be nine. Any number with a 9 in the one’s place (unit digit) would still have a nine in that place after being cubed.
29³=24,389
69³=328,509
Answer:
Step-by-step explanation:
she wrote it to solve the total amount spent on both T shirt.
30+6x=20+8x-8x
30+6x-8x=20
30-30-2x=20
-2x=20-30
-2x/-2=-10/-2
<u>x=5</u>
<u>Given</u>:
Let the two numbers be x and y.
Two numbers multiply to be -7 and add to be -6.
This can be written in equation as,
and
![x+y=-6](https://tex.z-dn.net/?f=x%2By%3D-6)
<u>Value of the two numbers:</u>
Let us determine the value of the two numbers using substitution method.
Substituting
in the equation
, we get;
![x(-6-x)=-7](https://tex.z-dn.net/?f=x%28-6-x%29%3D-7)
Simplifying, we get;
![-6x-x^2=-7](https://tex.z-dn.net/?f=-6x-x%5E2%3D-7)
![x^2+6x-7=0](https://tex.z-dn.net/?f=x%5E2%2B6x-7%3D0)
![(x+7)(x-1)=0](https://tex.z-dn.net/?f=%28x%2B7%29%28x-1%29%3D0)
![x=-7, 1](https://tex.z-dn.net/?f=x%3D-7%2C%201)
Thus, the values of x are x = 1,-7
When x = 1 , the equation
becomes ![y=-7](https://tex.z-dn.net/?f=y%3D-7)
When x = -7, the equation
becomes ![y=1](https://tex.z-dn.net/?f=y%3D1)
Therefore, the two numbers are 1 and -7